2019
DOI: 10.1111/1365-2745.13319
|View full text |Cite
|
Sign up to set email alerts
|

Below‐ground responses to insect herbivory in ecosystems with woody plant canopies: A meta‐analysis

Abstract: 1. Insect herbivory can have important consequences for the functioning of terrestrial ecosystems. Despite a growing recognition of the role of herbivores in above-ground-below-ground interactions, our current understanding is mainly restricted to studies of vertebrates in grassland and tundra ecosystems, while ecosystems with tree-like canopies (termed forests below) and invertebrates remain understudied.2. Here, we assess the current state of knowledge of one key aspect of plant-herbivore interactions by con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 66 publications
4
41
0
1
Order By: Relevance
“…Our findings agree with previously described cascading effects of reduced carbon assimilation by trees affecting belowground mutualists (Högberg et al 2001;Pec et al 2016;Kristensen et al 2020). In our study, insect defoliation was linked to changes in the soil fungal community structure and trophic function.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings agree with previously described cascading effects of reduced carbon assimilation by trees affecting belowground mutualists (Högberg et al 2001;Pec et al 2016;Kristensen et al 2020). In our study, insect defoliation was linked to changes in the soil fungal community structure and trophic function.…”
Section: Discussionsupporting
confidence: 93%
“…For example, a decline in primary productivity caused by insect defoliation could negatively affect ecosystem processes such as nutrient cycling through affecting belowground communities (Clemmensen et al 2015;Saravesi et al 2015;Kristensen et al 2020). Climate change is expected to increase the severity and frequency of insect outbreaks (Battisti et al 2005, Hódar & Zamora 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from grassland systems have shown that insect herbivory increases belowground allocation of photosynthates by their hosts, possibly to boost their nutrient uptake (Belovsky & Slade, 2000; Hamilton et al., 2008). Yet, in forest ecosystems, belowground C allocation by plants is reduced by aboveground insect herbivory (Frost & Hunter, 2008a; Kristensen et al., 2020), which represents a reduction in fast‐cycle processes. Moreover, the immediate induction in chemical plant defenses (Fürstenberg‐Hägg et al., 2013; Halitschke et al., 2008; Haukioja, 2005; Kessler et al, 2004) increase the decomposition time of the resulting litter (Chomel et al, 2016), although it is not clear to what extent these effects may be transient (Frost & Hunter, 2008b).…”
Section: Discussionmentioning
confidence: 99%
“…While less conspicuous than mammals, insect herbivores can exert a similar or even stronger control than mammals on ecosystem functioning (Hunter, 2001, Kristensen et al., 2020; Lovett et al., 2002; Risch et al., 2018; Silfver et al., 2020), particularly in forest ecosystems, where their impact is likely to intensify substantially with global change (Logan et al., 2003). Insect herbivory may cause early leaf abscission (Karban, 2007; Zvereva & Kozlov, 2014), leaf consumption (Galmán et al., 2018; Kozlov et al., 2015), alteration of aboveground versus belowground allocation of photosynthates (Ayres et al., 2004; Kristensen et al., 2020), and induction of plant defenses (Fürstenberg‐Hägg et al., 2013; Halitschke et al., 2008; Haukioja, 2005; Kessler et al, 2004). These effects alter the timing, quantities, and pathways of element fluxes, including the partitioning between fast‐ and slow‐cycle pathways through the decomposition foodweb (Frost & Hunter, 2004, 2007; Hunter et al., 2012; Kristensen et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There is thus a growing body of evidence that warmer conditions will lead to intensified insect herbivory, which could result in reduced growth of common woody plants at high latitudes. These growth reductions can result from direct losses of foliar area restricting photosynthetic gains (Björkman et al, 2000) but also via alterations in soil available resources and mycorrhizal status (Kristensen et al, 2020;Sandén et al, 2020).…”
Section: Pjmentioning
confidence: 99%